Exome of Radiation-induced Rat Mammary Carcinoma Shows Copy-number Losses and Mutations in Human-relevant Cancer Genes - MORIYAMA, HITOMI; DAINO, KAZUHIRO; ISHIKAWA, ATSUKO; IMAOKA, TATSUHIKO; NISHIMURA, MAYUMI; NISHIMURA, YUKIKO; TAKABATAKE, MASARU; MORIOKA, TAKAMITSU; INOUE, KAZUMASA; FUKUSHI, MASAHIRO; SHIMADA, YOSHIYA; KAKINUMA, SHIZUKO (Anticancer research, 2021)
Our understanding of cancer risk from neutron exposure is limited. We aimed to reveal the characteristics of mammary carcinomas induced by neutrons. Mammary carcinomas obtained from female Sprague-Dawley rats irradiated at 7 weeks of age with 0.97 Gy neutrons or 4 Gy γ-rays and from non-irradiated rats were classified into luminal and non-luminal subtypes by immunohistochemistry. Their mutational landscapes were determined by whole-exome sequencing. Neutrons significantly raised the incidence of luminal mammary carcinomas over the non-luminal subtype. Somatic mutations were identified in cancer genes involved in several signalling pathways, including Keap1/Nrf2, Pi3k/Akt and Wnt/β-catenin. Focal copy-number losses involving cancer genes were observed mainly in carcinomas from the irradiated rats. Neutrons increase the incidence of luminal mammary carcinomas, probably through gene mutations similar to those found in human breast cancers, and focal copy-number losses including cancer genes that are characteristics of radiation-induced mammary carcinomas.